Determination of Metal Contamination in Seafood from the Black, Marmara, Aegean and Mediterranean Sea Metal Contamination in Seafood - KUPLULU, O.; IPLIKCIOGLU CIL, G.; KORKMAZ, S. D.; AYKUT, O.; OZANSOY, G. (Journal of the Hellenic Veterinary Medical Society, 2018)
Seafood is one of the most important components of a healthy diet due to its composition. With the Black, Marmara, Aegean and Mediterranean Sea, Turkey has substantial sources of seafood. Seas are highly impacted by environmental pollution. Among these, heavy metal pollution has long been recognized as a serious problem for seafood. As heavy metals cannot be degraded, they are deposited, assimilated or incorporated in water, sediment and aquatic animals. By these properties, they can be transferred to humans through the food chain especially by the consumption of fish and shellfish. The aim of this study is to determine the concentrations of Cd, As, Pb and Hg levels in selected fish species and marine animals from all of the 4 seas of Turkey by using the ICP-MS technique, and to compare the results with the legislations safe limits. For this purpose, 13 different fish species, mussels and shrimps have been obtained from the Black, Marmara, Aegean and Mediterranean Seas. According to the results, metal concentrations decrease in the order As>Pb>Hg>Cd. In all the seas, the same order was found. Statistically significant differences were observed in the metal levels between fish species and the shellfish in all regions. Except for the two samples, all the results was found compatible with the Turkish Food Codex and European Commission Regulation limits. Arsenic levels were detected between 0,076-4,230 mg/kg within the samples. Cadmium levels were detected as higher than the limits in two samples obtained from the Mediterranean Sea, Scophthalmus maximus and Mullus barbatus species as 0,076 mg/kg and 0,064 mg/kg, respectively. The highest and the lowest levels of mercury and lead were measured as 0,005-0,405 and 0,015-0,405 mg/kg, respectively. The results obtained from this study revealed that, except for a few cases, the selected heavy metal concentrations in most samples were below the limits. Also, besides the mussels and the shrimps, there was no single type of fish that was consistently high in all metals. The examined seas and the seafood were found to be safe for human consumption.